Ultraviolet observations of the hydrogen coma of comet C/2013 A1 (Siding Spring) by MAVEN/IUVS. Issue 21 (5th November 2015) - Crismani, Matteo M. J.; Schneider, Nicholas M.; Deighan, Justin I.; Stewart, A. Ian F.; Combi, Michael; Chaffin, Michael S.; Fougere, Nicolas; Jain, Sonal K.; Stiepen, Arnaud; Yelle, Roger V.; McClintock, William E.; Clarke, John T.; et al.
Abstract: We used the Imaging Ultraviolet Spectrograph (IUVS) aboard the Mars Atmosphere and Volatile EvolutioN (MAVEN) orbiting spacecraft to construct images of the hydrogen coma of comet C/2013 A1 (Siding Spring) days before its close encounter with Mars. We obtain a water production rate of 1.1 ± 0.5 × 10 28  molecules/s and determine the total impacting fluence of atoms and molecules corresponding to the photodissociation of water and its daughter species to be 2.4 ± 1.2 × 10 4  kg. We use these observations to confirm predictions that the mass of delivered hydrogen is comparable to the existing reservoir above 150 km. Furthermore, we reconcile disparity between observations and predictions about the detectability of the hydrogen perturbation and thermospheric response. Key Points: We determine Comet Siding Spring's water production rate We determine the mass of gas that impacted Mars We revisit and reconcile predictions with our observations